Attitudes Towards Philippine English: The Case of ESL Teachers in Selected Provinces in Central Luzon, Philippines - Babanto, Marty G.; Babanto, Merlito D.; Bante, Maribeth A.; Camua, Rhea D.; De Leon, Mary Anne S.; Guinto, Gerald G.; Macalino, Marvin S.; Mangulabnan, Gerly O.; Mercado, Mary Flor A.; Natividad, Roberto R.; Fabian-Perona, Edlynne; Santos, Paulo Joseph P.; Torres, Mark Lan B.; Anicas, Roel P. (Future Science / FSH-PH Publications, 2023)
Language attitudes refer to individuals' views, judgments, and emotions regarding a language or linguistic variety. These attitudes are shaped by various factors such as cultural, social, historical, and political contexts. In the case of Philippine English, attitudes regarding this linguistic variant have shifted, reflecting evolving views and ideals within Philippine culture. Thus, the study aimed to provide insights into the social, cultural, and linguistic factors that shape attitudes towards Philippine English and contribute to a better understanding of language attitudes in multilingual societies. Both quantitative and qualitative methods were employed in the study, specifically the concurrent triangulation or convergent parallel design. The researchers used convenience sampling to identify 40 ESL teachers in selected provinces in Central Luzon, Philippines. The research instrument that the proponents utilized for this study is the survey questionnaire, and the data were analyzed through descriptive statistics and thematic analysis. Based on the quantitative findings, the data revealed that most ESL teachers strongly agree with the acceptance and utility of Philippine English in ESL instruction. Furthermore, the qualitative data presented that Philippine English promotes cultural understanding, student engagement, language empowerment, and a sense of belonging. It also enhances language skills, promotes cultural relevance and understanding, boosts communication and confidence, facilitates real-life application, and contributes to the professional growth of teachers. Finally, incorporating Philippine English in ESL instruction contributes to a more inclusive, engaging, and effective language learning experience for students. The researchers recommended offering professional development opportunities for ESL teachers, addressing the concerns of teachers who express disagreement and doubt regarding the utility of Philippine English, supporting teachers in adapting their teaching methods to effectively incorporate Philippine English, and encouraging ongoing professional growth and development among teachers in the field of Philippine English for ESL education.